IMPLEMENTASI MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT): HUNTER MAP UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPAS KELAS VI SD - Yuliana Safitri, Novita; Julianto; Ceffiriana, Paramita; Dardiri, Alfan; Hidayati, Fitria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research was conducted at SDN Pagesangan 426, where when observing class VI, many students were less active and critical during the learning process. In order to improve students' critical thinking skills, the researcher applied the Team Games Tournament learning model in the form of Hunter Map on the Human Movement Organ System material. The research subjects were 31 students in the 2024/2025 academic year. This type of research is classroom action research carried out in 2 cycles. Data collection techniques in this study were observation and tests. The results of students' critical thinking skills classically were obtained in the pre-cycle, namely 41.9%, cycle I 61.3% and cycle II 80.6%. Based on the results of this study, it can be concluded that the TGT model can improve the critical thinking skills of class VI students of SDN Pagesangan, especially on the material of the human movement organ system.